Women in Construction and the Workforce Investment Act: Evidence from Boston and the Big Dig. (December 2016) - Arcand, Carolyn
This article examines whether women's representation among senior-level construction jobs increased over time during a long-term, large-scale construction project in Boston, Massachusetts, and whether enactment of the Workforce Investment Act (WIA) has fostered support and connection to construction career opportunities for women in this metropolitan area. Results show that the proportion of hours worked by women in senior-level positions on the project was relatively high for a few years, followed by a general decline across all job types, and the WIA did not significantly enhance opportunities for women in construction.